2012
DOI: 10.1093/nar/gks656
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs are exported from malignant cells in customized particles

Abstract: MicroRNAs (miRNAs) are released from cells in association with proteins or microvesicles. We previously reported that malignant transformation changes the assortment of released miRNAs by affecting whether a particular miRNA species is released or retained by the cell. How this selectivity occurs is unclear. Here we report that selectively exported miRNAs, whose release is increased in malignant cells, are packaged in structures that are different from those that carry neutrally released miRNAs (n-miRNAs), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(158 citation statements)
references
References 85 publications
8
145
1
Order By: Relevance
“…In NSCLC, certain studies have shown the prognostic value of specific miRNAs in the plasma and serum (8-11). Furthermore, a focus has been placed on miRNAs that have also been identified in the exosome of plasma and serum in an unexpectedly stable form, which is protected from endogenous RNase activity (12)(13)(14). Exosomes are small membrane vesicles (30-100 nm) whose derivation lies in the luminal membranes of multivesicular bodies and which are released by fusion with the cell membrane (15).…”
Section: Introductionmentioning
confidence: 99%
“…In NSCLC, certain studies have shown the prognostic value of specific miRNAs in the plasma and serum (8-11). Furthermore, a focus has been placed on miRNAs that have also been identified in the exosome of plasma and serum in an unexpectedly stable form, which is protected from endogenous RNase activity (12)(13)(14). Exosomes are small membrane vesicles (30-100 nm) whose derivation lies in the luminal membranes of multivesicular bodies and which are released by fusion with the cell membrane (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings suggest that cancer cells release specialized EVs, enriched with miRNAs, which are not released by non-neoplastic cells [75] . Indeed, cancer patients often exhibit elevated levels of specific, circulating miRNA species.…”
Section: Mirnas As Biomarkers For Cancermentioning
confidence: 97%
“…For example, it was recently discovered that malignant cells could release miRNAs in larger exosomes that expressed different surface markers as compared to the exosomes released from normal non-cancerous cells. 111 Since studies such as the murine melanoma study outlined above, have shown that exosomes released from malignant cells can increase the metastatic properties of other cells 83,112 and since exosomes are known to contain mRNA, proteins and miRNAs, it suggests that secreted miRNAs, as well as any other proteins or mRNA, contained within the exosomes can non-cell autonomously alter the properties of cancer cells. Indeed, a study done by Taylor and colleagues 113 showed that tumor-derived exosomes isolated from sera of ovarian cancer patients contained a variety of miRNAs, both similar to and different from the miRNAs expressed by the tumor mass, including some that have been previously associated with increased metastasis in ovarian cancer.…”
Section: Epithelial-to-mesenchymal Transition and Metastasismentioning
confidence: 99%